MODEL EPIDEMI SIRS STOKASTIK DENGANSTUDI KASUS INFLUENZA - Nurlazuardini, Novia Nilam; Kharis, Muhammad; Hendikawati, Putriaji (Universitas Negeri Semarang, 2016)
Epidemic SIRS model is an epidemic model which illustrate the spread of disease from suscept to infected, and then become a recovered and become suscept again depend of the immunity. In this article, we dicussed epidemic stochastics SIRS model with embedding epidemic deterministic model, analysis of the model and the behavior of this disease in the future. To obtain the result of basic reproduction ration, Crump-Mode-Jagers process with embedding BGW branching process in some process. From the analysis and the simulation of the model were obtained , if ð‘…0 < 1 then the epidemic is extinct and if ð‘…0 â‰¥ 1 the epidemic is occurred. To illustrate the model simulation were carried out using Maple software. The model simulation give the same result with the analysis.